2015
DOI: 10.1515/biol-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the conserved GRG motif and decreasing activity of human RNase H2

Abstract: RNase H2 consists of three subunits (H2A, H2B and H2C) and is involved in the hydrolysis of RNA/DNA hybrids. The GRG motif in RNase H2 is highly conserved and recognizes the ribonucleotides misincorporated into dsDNA. The mutant G37S in the GRG motif of human RNase H2A was found to be correlated with Aicardi-Goutièressyndrome (AGS). In this study, 4 mutants (G37S, G37A, R38A and G39A) were prepared and their biochemical properties of secondary structure, activity and binding affinity with substrate were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The purified R351A DDX3X mutant ( Supplementary Figure S2a ), displayed a k cat / K m reduction of 5.5-fold in helicase activity if compared to wild type ( Supplementary Figure S2b ). More interestingly, R351A displayed also >90% reduced nuclease activity with respect to the wild type (Figure 3D , E ), similarly to the reported strongly reduced nuclease activity of RNaseH2 mutant R38A ( 35 ). To further identify other domains/residues responsible for the nuclease activity of DDX3X, we used a series of DDX3X mutants (Figure 3C and Supplementary Figure S2a ) available in our laboratory.…”
Section: Resultssupporting
confidence: 81%
“…The purified R351A DDX3X mutant ( Supplementary Figure S2a ), displayed a k cat / K m reduction of 5.5-fold in helicase activity if compared to wild type ( Supplementary Figure S2b ). More interestingly, R351A displayed also >90% reduced nuclease activity with respect to the wild type (Figure 3D , E ), similarly to the reported strongly reduced nuclease activity of RNaseH2 mutant R38A ( 35 ). To further identify other domains/residues responsible for the nuclease activity of DDX3X, we used a series of DDX3X mutants (Figure 3C and Supplementary Figure S2a ) available in our laboratory.…”
Section: Resultssupporting
confidence: 81%
“… 25 RNASEH2A-G37S is within the catalytic subunit, whereas RNASEH2C-K69W is in a non-catalytic subunit but it is still very close to the Subunit A-catalytic site within the RNase H2 complex. 14 , 37 The yeast ortholog mutations rnh201 -G42S and rnh203 -K46W were created in S. cerevisiae in the BY4742 background ( MAT α his3 Δ1 leu2 Δ0 lys2 Δ0 ura3 Δ0) using the delitto perfetto technique. 38 We built 14 ribose-seq libraries of rNMPs embedded in the genomic DNA of yeast strains carrying wild-type RNase H2, rnh201 -G42S, rnh203 -K46W, or rnh201 Δ genotype ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…The G37S mutation in human RNase H2A is a common mutation in individuals with AGS, located in a conserved region of the protein, nearby the catalytic site. 37 This specific mutation affects the catalytic activity of the RNase H2 enzyme, impairing its ability to cleave rNMPs 42 and process RNA/DNA hybrids effectively. 31 , 43 In our analyses, the RNase H2A-G37S mutant ortholog in yeast, Rnh201-G42S, shows lack of catalytic activity because of the highly increased rNMP percentage in nuclear DNA relative to the rNMP presence in mitochondrial DNA, as observed for rnh201 Δ libraries ( Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%
“…The G37S mutation in human RNase H2A has been identified in individuals with AGS and is in the highly conserved catalytic site of the RNase H2 enzyme 28 .This specific mutation affects the catalytic activity of the RNase H2 enzyme, impairing its ability to cleave rNMPs 29 and process RNA/DNA hybrids effectively 30 . In our analyses, the RNase H2A-G37S mutant ortholog in yeast, Rnh201-G42S, reflects lack of catalytic activity because of the highly increased rNMP percentage in nuclear DNA relative to the rNMP presence in mitochondrial DNA, as observed for rnh201 △ libraries (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…In the mononucleotide-heatmap analysis of rNMPs present on the leading vs lagging strands in the 4-10-kb region around early-firing ARSs, we do not detect strand-biased composition for the AGS mutant libraries, as detected for wild-type and rnh201△ libraries of wild-type mutant Pols 17 . 28 It has been found that rNMPs have markedly distinct dinucleotide frequencies on the leading and lagging strands 4-10-kb upstream and downstream of early-firing ARSs in rNMP libraries of rnh201△ cells expressing wild-type or mutant forms of DNA polymerase (Pol) δ or Pol ε. Leading and lagging strand-dinucleotide patterns show signatures of incorporation due to the activity of DNA Pol ε and Pol δ on these strands, respectively.…”
Section: S Cerevisiae Orthologs Of Rnase H2c-r69w and Rnase H2a-g37s ...mentioning
confidence: 99%